Proses Pengeringan Kunyit (Curcuma domestica Val) dan Sifat Fisik Tepung yang Dihasilkan - Sari, Fadilah Kurnia; Tamrin, Tamrin; Kuncoro, Sapto; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2024)
Currently, the public's tendency to consume traditional medicines is quite high, based on the existing potential, the medicinal product that can be widely developed is the turmeric plant. Turmeric stored in dry powder form has a lower curcumin content than fresh turmeric, namely containing 3-5% curcumin. Therefore, storing turmeric in powder form with a low water content is one way to maintain the quality of turmeric. This research was carried out with three treatments with three repetitions, including drying with a tool using solar energy, drying with a tool using electrical energy, drying with a tool using solar energy and electrical energy (hybrid), and drying using a winch (as a control). . Observations carried out to determine the physical properties of the turmeric flour produced were in the form of color measurements, bulk density measurements, air absorption measurements, stack angle measurements, and measurements of the degree of fineness of the material. Based on the results of the tests carried out, drying using solar and electric energy (hybrid) takes 8 hours, followed by testing using electric energy which takes 10 hours. The flouring process is carried out by blending dried turmeric for 5 minutes. The temperature and type of treatment carried out during the turmeric drying process did not have a significant effect on the turmeric flour produced. Keywords: drying, hybrid, flour, turmeric.